Trends in gabapentinoid prescribing: A nationwide Danish drug utilization study - Pottegård, Anton; Rasmussen, Lotte; Olesen, Morten; Skov Sørensen, Anne Mette; Ennis, Zandra Nymand; Kane, Joseph; Baxter, Sarah; Hicks, Blánaid (British journal of clinical pharmacology, 2025)
Aims Pregabalin and gabapentin are increasingly used for pain and other conditions. Concerns exist about overuse as well as potential misuse and abuse. To guide rational prescribing practices, we provide detailed nationwide data on the use of gabapentinoids in Denmark. Methods We conducted a nationwide descriptive drug utilization study using the Danish healthcare registries to describe the use of gabapentinoids among Danish adults 2010–2023. We described overall use patterns, temporal trends, user characteristics, skewness of use, treatment duration and concomitant medication use. Results The prevalence of gabapentinoid use increased almost four‐fold from 11 per 1000 adults in 2010 to 41 in 2023 with the highest use among individuals aged 80+ years (96 per 1000 in 2023). Gabapentin and pregabalin were used equally. The median age of users increased from 58 years in 2010 to 63 years in 2023, while a decline was observed in the proportion with concomitant use of other drug classes, including benzodiazepines or opioids. Only 7% of patients were continuously treated for 3 years following initiation, while 22% were currently treated after 3 years (allowing treatment breaks). The use of gabapentinoids were somewhat skewed with 1% of users accounting for 7.3% of use in 2023. Conclusion The use of gabapentinoids has increased dramatically in recent years, in particular, among the elderly, and adherence was low. Increased attention to the increasing use of gabapentinoids is warranted to ensure rational use of this drug class.